An Analysis of Communication Approach in Millie Bobby Brown and Maisa Silva’s UNICEF Interview on Young Women’s Rights - Robbika, Sabbihisma; Rikza, Nur Qolbiyatur; Swasono, Endratno Pilih (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The young generation in some parts of the world still struggle through numerous challenges to gain their rights and welfare. UNICEF, as an organization that works particularly in children’s concerns, plays a critical role by conducting campaigns to promote their rights, notably on young women’s rights. This study aims to reveal the language style used in a UNICEF interview featuring two UNICEF ambassadors, Millie Bobby Brown and Maisa Silva, and how messages and meaning on young women’s rights are communicated through Dell Hymes’ SPEAKING model. The data from the interview were taken from the UNICEF Brasil YouTube channel and were transcribed and analyzed, and were presented using a qualitative descriptive method. The researchers examine the communicative elements using the ethnography of the communicative approach developed by Dell Hymes, including the setting or scene, the participants, the end purposes, the act sequence, the key style, the instrumentalities, the norms, and the genre. The result of this study shows that the language style used by Millie Bobby Brown and Maisa Silva can frame the discussion to address the audience. In addition, the researchers find that Dell Hymes’ theory of the SPEAKING model suits how the messages in the interview effectively highlight young women’s struggle for their rights.